Design of Floating Crane Ship Maintenance Strategy Based on the Influence of Preventive Maintenance, Total Quality Management on Operational Performance Using the PLS-SEM Method - Muhammad Yusuf Nurdin; Endang Chumaidiyah; Iphov Kumala Sriwana (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of preventive maintenance and Total Quality Management (TQM) on the operational performance of floating crane vessels at PT XYZ and to develop a more systematic and measurable maintenance strategy. The research focuses on the FC 02 floating crane unit, which experienced high downtime and fluctuating operational availability. A quantitative approach was employed using a survey method involving 228 respondents directly engaged in floating crane operations and maintenance activities. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The results indicate that preventive maintenance has a positive and significant effect on operational performance, particularly in improving equipment reliability and reducing downtime. Furthermore, Total Quality Management shows a stronger and more dominant positive influence on operational performance, highlighting the critical role of managerial systems, leadership commitment, and continuous improvement practices. The findings confirm that integrating effective preventive maintenance with consistent TQM implementation can significantly enhance the operational performance of floating crane vessels. This study provides both theoretical contributions to maritime maintenance literature and practical insights for designing a Planned Maintenance System (PMS) to support sustainable operational performance.